2018
DOI: 10.1007/s15010-018-1150-4
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, management and outcome of varicella in pregnancy: a 20-year experience at the Tuscany Reference Centre for Infectious Diseases in Pregnancy

Abstract: Data from 215 pregnant women exposed to varicella and 276 with varicella observed at the Tuscany Reference Center for Infectious Diseases in Pregnancy, Florence, Italy, in the period 1997-2016 were retrospectively collected. The risk of developing varicella was lower in exposed women who received varicella zoster immunoglobulin compared with those who did not receive it [42% (21 of 50) vs 72% (13 of 18); p = 0.0263]. Typical congenital varicella syndrome was observed in 1.56% of fetuses/neonates born from preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 10 publications
0
11
0
4
Order By: Relevance
“…An Italian retrospective study reported that in pregnant women exposed to VZV, 72% of those who did not receive post-exposure prophylaxis developed varicella compared with 42% of those who received VZIG (discontinued 2006) [35]. In the current study, the rate of varicella in pregnant women was much lower, at 7.3%.…”
Section: Discussionmentioning
confidence: 44%
“…An Italian retrospective study reported that in pregnant women exposed to VZV, 72% of those who did not receive post-exposure prophylaxis developed varicella compared with 42% of those who received VZIG (discontinued 2006) [35]. In the current study, the rate of varicella in pregnant women was much lower, at 7.3%.…”
Section: Discussionmentioning
confidence: 44%
“…In the 2 available studies of pregnant women who received postexposure prophylaxis with VARIZIG, 3,4 the incidence of varicella was low, especially compared with findings from a 20-year retrospective study of postexposure prophylaxis with varicella zoster immune globulin (VZIG, discontinued in 2006) that reported varicella incidence of 42% vs 72% among those who did not receive postexposure prophylaxis. 5 In each study, there was a similar varicella incidence, regardless of the timing of the administration after VZV exposure. No cases of varicellarelated pneumonia occurred in either study.…”
Section: Discussionmentioning
confidence: 86%
“…Varicella-zoster virus (VZV) is a herpesvirus that is transmitted by respiratory droplets, direct contact with skin lesions, and transplacentally during pregnancy [30]. Infants that are exposed to VZV during the last few weeks of pregnancy may develop neonatal varicella which can be quite severe; congenital varicella syndrome (CVS) develops in infants exposed during the pregnancy, with the risk being highest if the exposure occurs in the first trimester [30]. Infants exposed after 20 weeks' gestation only have about 2% chance of developing CVS [31].…”
Section: Varicella-zostermentioning
confidence: 99%